Empowering and rights-based approaches to working with older people - Blundell, Barbara (Allen & Unwin, 2009)
This chapter will examine critical social work with older people, specifically as it relates to the area of the abuse and mistreatment of older people. Several critical theories will be discussed, including feminism, structural social work, and human rights based advocacy and empowerment. Critical theory aims for some manner of positive outcome for the individuals or groups identified. Thus, it is a useful perspective within which to consider ways of responding to elder abuse, both at the micro and macro level. In exploring critical social work with older people, the diversity of the older population will be highlighted and the social context discussed. An elder abuse case study will be explored; highlighting the effectiveness of rights focused advocacy and empowerment interventions.